Edukasi Kesehatan Reproduksi Remaja dalam Upaya Mencegah Stunting - Citra Elly Agustina; Diah Winatasari; Atik Maria (Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting is a major nutritional problem among toddlers in Indonesia that remains unresolved. According to the 2024 Indonesian Nutritional Status Survey, 16.8% of toddlers are underweight, 19.8% are stunted, and 6.2% are malnourished. According to the WHO, the interaction of various factors causing stunting consists of four factors: family and household factors, breastfeeding, complementary feeding, and infection. One family and household factor can be caused by teenage pregnancy or unwanted pregnancies. These problems begin with premarital sexual behavior, which leads to pregnancy and abortion. One effort to address adolescent reproductive health issues is through the provision of adolescent reproductive health services. Adolescent reproductive health services aim to prevent and protect adolescents from risky sexual behavior that can impact reproductive health. The methods used include education, discussion, and counseling related to adolescent reproductive health and stunting prevention. The results of reproductive health education resulted in a 29-point increase in scores.